Ypd1 Is an Essential Protein of the Major Fungal Pathogen Aspergillus fumigatus and a Key Element in the Phosphorelay That Is Targeted by the Antifungal Drug Fludioxonil - Schruefer, Sebastian; Spadinger, Anja; Kleinemeier, Christoph; Schmid, Laura; Ebel, Frank (Frontiers in Fungal Biology, 2021)
Aspergillus fumigatus is a major fungal pathogen causing life threatening infections in immunocompromised humans and certain animals. The HOG pathway is for two reasons interesting in this context: firstly, it is a stress signaling pathway that contributes to the ability of this pathogen to adapt to various stress conditions and secondly, it is the target of antifungal agents, such as fludioxonil or pyrrolnitrin. In this study, we demonstrate that Ypd1 is an essential protein in A. fumigatus. As the central component of the multistep phosphorelay it represents the functional link between the sensor histidine kinases and the downstream response regulators SskA and Skn7. A GFP-Ypd1 fusion was found to reside in both, the cytoplasm and the nucleus and this pattern was only slightly affected by fludioxonil. A strain in which the ypd1 gene is expressed from a tet-on promoter construct is unable to grow under non-inducing conditions and shows the characteristic features of A. fumigatus wild type hyphae treated with fludioxonil. Expression of wild type Ypd1 prevents this lethal phenotype, but expression of an Ypd1 mutant protein lacking the conserved histidine at position 89 was unable to do so, which confirms that A. fumigatus Ypd1 is a phosphotransfer protein. Generation of ypd1tet−on variants of several mutant strains revealed that the lethal phenotype associated with low amounts of Ypd1 depends on SskA, but not on TcsC or Skn7. The ΔsskA ypd1tet−on, but not the ΔsskAΔskn7 ypd1tet−on mutant, was sensitive to fludioxonil, which underlines the importance of Skn7 in this context. We finally succeeded to delete ypd1, but only if sskA and skn7 were both inactivated, not in a ΔsskA single mutant. Hence, a deletion of ypd1 and an inactivation of Ypd1 by fludioxonil result in similar phenotypes and the two response regulators SskA and Skn7 are involved in both processes albeit with a different relative importance.